The origin of surfactant amphiphilicity and self-assembly in protic ionic liquids. Issue 11 (14th August 2015) - Dolan, Andrew; Atkin, Rob; Warr, Gregory G.
Abstract : Surfactant alkyl chain, head-group and counterion solvation in protic ionic liquids differs from water, affecting micelle formation and structure. Abstract : The nature of amphiphilic self-assembly in alkylammonium protic ionic liquids (PILs) is examined by systematically varying the ionic structure and composition, H-bonding capacity, and nanostructure of both the PIL and micelle-forming cationic surfactant, and contrasted with self-assembly in water. Using small-angle neutron scattering, micelle structure and concentrations are determined for primary – quaternary dodecylammonium salts in nitrate and thiocyanate PILs. While the solvophobic driving force depends only on the average polarity of the PIL, surprisingly strong, specific interactions of the head group and counterion with the PIL H-bond network are found. This suggests the importance of developing designer amphiphiles for assembling soft matter structures in PILs.